Microbiota dynamics and source tracing during the growing, aging, and decomposing processes of Eucommia ulmoides leaves - Shao, Qiuyu; Dong, Chunbo; Han, Yanfeng; Zhang, Yanwei (Frontiers in Microbiology, 2024)
Eucommia ulmoides, an important tree, faces serious threat to its growth from environmental stress, particularly climate change. Using plant microbes to enhance host adaptation to respond climate change challenges has been recognized as a viable and sustainable strategy. However, it is still unclear how the perennial tree microbiota varies across phenological stages and the links between respective changes in aboveground and belowground niches. Here, we sequenced 27 root and 27 leaf samples of E. ulmoides using 16S rRNA and ITS amplicon sequencing techniques. These samples were obtained from the three main phenological stages of leaves, including leaf growing, aging and decomposing stages. Results showed that the diversity, composition, and function of the leaf microbiota of E. ulmoides showed more obvious changes at three phenological time points compared to roots. Regarding alpha diversity, the root microbiota showed no difference across three sampling stages, while the leaf microbiota varied with sampling stages. Regarding beta diversity, the root microbiota clustered from different sampling stages, while the leaf microbiota exhibited distinct separation. Regarding composition and function, the dominant taxa and main functions of the root microbiota were the same in three sampling stages, while the leaf microbiota in the decomposing stage was obviously different from the remaining two stages. Additionally, taxa overlap and source-sink relationship existed between E. ulmoides microbiota. Specifically, the degree of overlap among root microbiota was higher than that of leaf microbiota in three sampling stages. The bidirectional source-sink relationship that existed between the root and leaf niches varied with sampling stage. During the leaf growing and aging stages, the proportion of microbial members migrating from roots to leaves was higher than the proportion of members migrating from leaves to roots. During the leaf decomposing stage, the migration characteristics of the fungal community between the root and leaf niches maintained the same as in the remaining two stages, but the proportion of bacterial members migrating from leaves to roots was significantly higher than that of members migrating from roots to leaves. Our findings provide crucial foundational information for utilizing E. ulmoides microbiota to benefit their host under climate change challenges.